Peran Guru Pendidikan Agama Kristen Terhadap Misi Kristen: Upaya Aktualisasi Amanat Agung - Meliani Konda Betu; Yonatan Alex Arifianto (LOGON ZOES: Jurnal Teologi, Sosial dan Budaya, 2022)
As a Christian religious educator, you have a very important role in the process of increasing the spirituality of students who continue to have faith in Jesus. Moreover, it also educates students to preach the good news. However, the fact is that most teachers of Christian Religious Education have not fulfilled their responsibilities as teachers who have the task of preaching or carrying out the mandate of the Great Commission. In this case, the writer uses descriptive qualitative method with a literature study approach, with the following conclusions. The role of Christian Religious Education teachers in the mission should be one of the main goals in shaping or providing direction to students about their faith and spiritual growth. A Christian Religious Education teacher must also have a personal relationship with the Lord Jesus, because with a relationship with God, every teaching given to students can also be understood and understood by them and also, they can implement it in the lives of students in their lives. The growth of students' faith is a very important element in their lives, where through the growth of faith students can become blessings and witnesses through their lives. AbstrakSebagai pendidik agama Kristen memiliki peran yang sangat penting dalam proses untuk meningkatkan spritualitas naradidik yang berlanjut pada iman kepada Yesus. Terlebih juga mendidik muridnya untuk untuk memberitakan kabar baik. Namun faktanya kebanyakan guru Pendidikan Agama Kristen belum memenuhi tanggung jawabnya sebagai seorang guru yang memiliki tugas dalam memberitakan atau menjalankan mandat amanat agung. Dalam hal ini penulis menggunakan metode kualitatif deskritif dengan pendekatan studi literatur, dengan kesimpulan sebagai berikut, Peran guru Pendidikan Agama Kristen dalam misi harus menjadi salah satu tujuan utamanya dalam membentuk ataupun memberikan arahan kepada para peserta didik tentang pertumbuhan iman dan kerohanian mereka. Seorang guru Pendidikan Agama Kristen juga harus memiliki hubungan pribadi dengan Tuhan Yesus, karena dengan adanya hubungan dengan Tuhan maka setiap ajaran yang diberikan kepada para peserta didi juga dapat dimengerti dan dipahami oleh mereka dan juga mereka dapat mengimplementasikannya dalam kehidupan para peserta didik dalam kehidupannya. Pertumbuhan iman para peserta didik merupakan unsur yang sangat penting dalam kehidupannya, dimana lewat pertumbuhan iman maka peserta didik dapat menjadi berkat dan saksi lewat kehidupannya.